COMPREHENSIVE REVIEW OF INTERVENTIONS TARGETING INFECTIOUS DISEASE PREVENTION AND CONTROL, EMPHASIZING THE COLLABORATIVE EFFORTS OF PHARMACY, EPIDEMIOLOGY, AND SOCIAL WORK PROFESSIONALS IN COMMUNITY OUTREACH AND EDUCATION. - Saleh Hatim Almansour, Ali Saleh Hadi Almansour, Hassan Yahia Ali Alsalah, Ali Yahia Ali Alsalah, (Chelonian Research Foundation, 2022)
Infectious diseases are the biggest global challenge to public health and require flawless and balanced prevention and control. Collaborative work among pharmacy, epidemiology, and social work professionals is required in implementing infectious disease prevention campaigns involving the community, especially in the domains of health education, counselling, and outreach. The review evaluates interventions jointly applied by both healthcare disciplines that are at the center of this work. The priorities and approaches shown through the literature are reinforced, and the use of tables, figures, and graphs further demonstrates the effectiveness of multidisciplinary engagements in disease surveillance and control. Collaborative efforts will be encouraged by providing suggestions to upgrade them and dealing with the complex challenges of an ever-changing future world. Keywords: Infectious diseases, prevention, control, pharmacy, epidemiology, social work, collaboration, community outreach, education.